Expert Opinion on Managing Chronic HCV Infection in Patients with Type 2 Diabetes Mellitus. (January 2018) - Adinolf, Luigi Elio; Jacobson, Ira; Bondin, Mark; Cacoub, Patrice
Type 2 diabetes mellitus (T2DM) has been identified as an extrahepatic manifestation of chronic HCV infection. Conversely, in the context of chronic HCV infection, T2DM can accelerate the course of HCV-induced liver disease leading to increased risk of fibrosis, cirrhosis and hepa-tocellular carcinoma. The presence of T2DM negatively impacts the efficacy of interferon-based antiviral therapy, but real-world data with high-efficacy direct-acting antiviral therapies suggest high viral clearance rates in T2DM patients. In HCV-infected individuals, viral eradication is associated with a reduced risk of de novo T2DM in non-diabetic patients and beneficial metabolic changes in patients with T2DM, highlighting the importance of antiviral treatment and physician awareness of this association.